Presence of NaI in PEO/PVdF-HFP blend based gel polymer electrolytes for fabrication of dye-sensitized solar cells - Zebardastan, N.; Khanmirzaei, M.H.; Ramesh, S.; Ramesh, K. (Elsevier, 2017)
Poly(vinylidene fluoride-co-hexafluoro propylene) copolymer (PVdF-HFP) and polyethylene oxide (PEO) blend gel polymer electrolytes (GPEs) containing ethylene carbonate (EC) and propylene carbonate (PC) as solvent with different concentrations of sodium iodide (NaI) salt are prepared. Effect of sodium iodide (NaI) on the gel polymer electrolyte system is investigated by using electrochemical impedance spectroscopy (EIS), temperature-dependence ionic conductivity, X-ray diffraction (XRD) and FTIR studies. The highest ionic conductivity value for the gel polymer electrolytes are 6.38 mS cm−1 in the presence of 100 wt% of sodium iodide (NaI) salt with respect to weight of PEO/PVdF-HFP polymer blend. The temperature-dependent ionic conductivity study indicates that the gel polymer electrolyte system follows the Arrhenius model. Dye-sensitized solar cells (DSSCs) are fabricated using gel polymer electrolytes and tested under Sun simulator. The highest energy conversion efficiency value of 5.67% is obtained after the addition of 100 wt% of sodium iodide (NaI) salt.